ANALISIS POTENSI ATRAKSI AGROWISATA DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Apri Suprianto; Silfeni Silfeni; Pasaribu Pasaribu (Journal of Home Economics and Tourism, 2018)
The purpose of the research is to know the potential of agro-tourism in Lembah Gumanti, Solok rejency. The type of this research is qualitative research in using observation method, interview and dokumnetasi. Determination of informant using Snow-ball Sampling the are: head of tourism pfficial, 2 persons from agriculture official, 5 farmers and local community in Lembah Kecamatan Lembah Gumanti, solok regency. This research concluded: 1) strength is the temperature are clean, the sufficient clean water, fertile soil, State of the State of nature, the area is thick with customs. The process of planting and harvesting vegetables, fruit and flowers still traditional. 2) Beside that, the opportunities is agro tourism at Lembah Gumanti distrisk, the presence of local community organizations to support agro tourism, there are lot of supporting tourist attractions in Lembah Gumantiss district, Solok Regency.